Digitalization of Financial Reports in BUMDES in Gunungsari District - Rohadi, Akbar Fitra; Indriani, Eni (International Journal of Business and Applied Economics, 2024)
This research aims to evaluate the implementation of digitalization of financial reports in Village-Owned Enterprises (BUMDes) in Gunungsari District. Digitizing financial reports is an effort to increase transparency, accuracy and efficiency in BUMDes financial management. The research method used is a qualitative approach, which involves in-depth interviews with BUMDes managers in Gunungsari District and direct observation. The results of this research show that BUMDes in Gunungsari sub-district have implemented digital-based technology, but this is only for promotional and marketing activities, but for financial reports they still use a simple system.